2018
DOI: 10.1128/aac.00722-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activity of a Novel Catheter Lock Solution against Bacterial and Fungal Biofilms

Abstract: Central-line-associated bloodstream infections are increasingly recognized to be associated with intraluminal microbial biofilms, and effective measures for the prevention and treatment of bloodstream infections remain lacking. This report evaluates a new commercially developed antimicrobial catheter lock solution (ACL), containing trimethoprim (5 mg/ml), ethanol (25%), and calcium EDTA (Ca-EDTA) (3%), for activity against bacterial and fungal biofilms, using and (rabbit) catheter biofilm models. Biofilms were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Lown et al reported that a lock solution with micafungin, ethanol, and doxycycline inhibited C. albicans and mixed C. albicans-S. aureus biofilms. Beforehand, it was also confirmed the great in vitro activity of the same drugs as single agents for the prevention and treatment of C. albicans biofilms [177][178][179][180]. In this recent work, it was reported that a solution with 2% (v/v) ethanol, 0.01565 µg/mL micafungin, and 800 µg/mL doxycycline reduced metabolic activity (98%), with no fungal regrowth, applied once to prevent fungal biofilm formation.…”
Section: Innovative Treatments Of Other Diseasesmentioning
confidence: 62%
“…Lown et al reported that a lock solution with micafungin, ethanol, and doxycycline inhibited C. albicans and mixed C. albicans-S. aureus biofilms. Beforehand, it was also confirmed the great in vitro activity of the same drugs as single agents for the prevention and treatment of C. albicans biofilms [177][178][179][180]. In this recent work, it was reported that a solution with 2% (v/v) ethanol, 0.01565 µg/mL micafungin, and 800 µg/mL doxycycline reduced metabolic activity (98%), with no fungal regrowth, applied once to prevent fungal biofilm formation.…”
Section: Innovative Treatments Of Other Diseasesmentioning
confidence: 62%
“…Recently, a 4% tetrasodium ethylenediamine tetraacetic acid (EDTA) lock solution was approved by Health Canada to maintain patency and decrease the risk of bacterial colonization and biofilm formation within CVADs. EDTA has been used for decades as a powerful anticoagulant preventing clot formation in vitro ( 22 , 23 ) and is still being used in this capacity today ( 24 ). However, the form of EDTA most often used is the disodium salt, which has reduced antimicrobial properties ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the CLS with ethanol that reduced the incidence of CRBSI has also been shown to sterilize biofilms of gram-positive and gram-negative bacteria and fungal pathogens in vitro. Therefore, ethanol at low concentrations for a short time has higher efficacy than conventional antibiotics at high concentrations for a long period to treat CRBSI (Qu et al, 2009;Chandra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%